Partial replacement of corn grain by hydrogenated oil in grazing dairy cows in early lactation - Salado, E. E. (2004)
Thirty-six grazing dairy cows were used to determine milk production and composition, and dry matter and energy intake when corn grain was partially replaced by hydrogenated oil in the concentrate. Four additional cows, each fitted with a ruminal cannula, were used in a crossover design to evaluate effects of supplemental fat on rumen environment and pasture digestion. All cows grazed mixed pastures with an herbage allowance of 30 kg dry matter/cow per day. The control group was fed a concentrate containing corn grain (4.49 kg dry matter/cow per day) and fishmeal (0.37 kg dry matter/cow per day), whereas the other group (fat) received a concentrate containing corn grain (2.87 kg dry matter/cow per day), fishmeal (0.37 kg dry matter/cow per day) and fat (0.7 kg dry matter/cow per day). The fat was obtained by hydrogenation of vegetable oils (melting point 58 to 60 degrees C, 30.3% C16:0, 34.9% C18:0, 21.8% C18:1, 3.3% C18:2). Supplemental fat increased milk production (control = 23.7 vs. fat = 25.0 kg/cow per day), fat-corrected milk (control = 22.5 vs. fat = 24.5 kg/cow per day), milk fat content (control = 3.64% vs. fat = 3.86%) and yields of milk fat (control = 0.86 vs. fat = 0.97 kg/cow per day) and protein (control = 0.74 vs. fat = 0.78 kg/cow per day). Milk percentages of protein, lactose, casein, cholesterol, and urea nitrogen were not affected. Pasture DMI and total DMI of pasture and concentrate and estimated energy intake were unchanged. No differences in loss of body weight or body condition score were detected. Plasma concentrations of nonesterified fatty acids, somatotropin, insulin, and insulin-like growth factor were not affected by supplemental fat. Concentrations of plasma triglyceride and total cholesterol were increased by supplemented fat, and no changes in plasma glucose and urea nitrogen were observed. The acetate-to-propionate ratio was higher in rumen fluid of cows that consumed fat (fat = 3.39 vs. control = 3.27). In situ pasture NDF degradation was not affected. The partial replacement of corn grain with fat improved the productive performance of early-lactation cows grazing spring pastures. No negative effects of supplemental fat on ruminal fiber digestion were detected.